Physiotherapy of women after mastectomy - Śniegowska, Wiktoria; Ziółkowska, Anna; Wojtczak, Paweł; Ciecierska, Dominika; Wrzesiński, Bartłomiej; Piechocka, Edyta (Journal of Education, Health and Sport, 2018)
Physiotherapy of patients after mastectomy is a complex process. It includes not only physical exercises, but also other physiotherapy treatments, such as hydrotherapy, physical therapy, massage, kinesiotaping and psychological therapy. The best results brings the the early introduction of rehabilitation to the patients, before the procedure, when they learn how to properly perform exercises, and improve the performance of the muscle pump and prevent blockages by circulatory and respiratory exercises, which are the basis of kinesiotherapy.